Homestay owners acceptance of 360 degree panoramic views for homestay advertisement in Changlun - Selvakumar, Tharisini; Yaakob, Mazri (Universiti Utara Malaysia, 2020)
The homestay advertisement in Changlun still using the common advertisement method such as distributing brochure and pamphlet to peoples, presenting house model and the most advance is showing a walkthrough video around the house to potential customer. 360 Degree Panoramic View is growing in popularity as a way of marketing in various field of business around the world. 360 Degree Panorama View photos are effective for showing off vistas, internal architecture and more in a dramatic fashion that replicates the experience of being there. The main propose of this project is to find out the acceptance of homestay owners on the use of 360 Degree Panorama View for house advertisements. This research is conduct in qualitative methods. The interview was done face to face. Moreover, transcribe have used as the method analysis. The homestay owners strongly believe that this development makes better future. Technology Acceptance Model is the information system’s theory which used in this research to identify how house developers come to accept and use this 360 Degree Panorama View technology in house marketing.